Basics and Structure of Project Writing in Mathematics - K.C., Durga Jang; Ghimire, Santosh (Journal of Nepal Mathematical Society, 2020)
In this article various components of undergraduate project writing in mathematics are listed and discussed. We focus on the basics of a mathematical project writing in which we describe the necessity and usefulness of project writing. We then describe the structure of the project stating its various com- ponents. Finally we give some sample project topics. This article is intended for the students of bachelor level and faculties of mathematics among various universities in Nepal.